Clinical validation of the novel CLIA-CA-62 assay efficacy for early-stage breast cancer detection - Sekacheva, Marina; Boroda, Alexander; Fatyanova, Anastasia; Rozhkov, Alexander; Bagmet, Nikolai (Frontiers in Oncology, 2023)
Background Without organized screening programs up to 60-70% of breast cancers are diagnosed at advanced stages that have significantly lower five-year survival rate and poorer outcomes, which is a serious global public health problem. The purpose of the blind clinical study was the assessment of the novel in-vitro diagnostic chemiluminescent CLIA-CA-62 assay for early-stage breast cancer detection. Methods Blind serum samples of 196 BC patients with known TNM staging, 85% with DCIS, Stage I & IIA, and 73 healthy control subjects were analyzed with the CLIA-CA-62 and CA 15-3 ELISA assays. Results were also compared to the pathology findings and to published data from mammography, MRI, ultrasound, and multi-cancer early detection test (MCED). Results The CLIA-CA-62 overall sensitivity for BC was 92% (100% for DCIS) at 93% specificity and it decreased in invasive stages (Stage I=97%, Stage II=85% and Stage III=83%). For the CA 15-3 assay sensitivity was 27-46% at 80% specificity. Sensitivity for mammography was 63-80% at 60% specificity, depending on the stage and the parenchymal density. Conclusion These results demonstrate that CLIA-CA-62 immunoassay could prove useful as a supplement to current mammography screening and other imaging methods, thus increasing the diagnostic sensitivity in DCIS and Stage I breast cancer detection.